DETEKSI LIMBAH ACID SLUDGE MENGGUNAKAN METODE RED EDGE BERBASIS DATA PENGINDERAAN JAUH - Haryani, Nanik Suryo; Hidayat, Hidayat; Sulma, Sayidah; Pasaribu, Junita Monika (Institut Teknologi Sepuluh Nopember, 2014)
In line with the growing industry and population, the contamination of hazardous and toxic waste material increased. The increases is triggered by inappropriate handling of household and industry sector. The monitoring or detection of contaminated area or zone is very crucial to identify the areas of dispersion of the hazardous waste material. Remote sensing is one of applicable tool for detecting purposes. Several research has utilized remote sensing data to detect the contaminated areas by vegetation index, surface temperature as well as other indexes. This research proposes the red edge method from Landsat TM data to detect the hazardous waste material contamination in Pertamina RU-V Balikpapan. Based on the executed review, it is acknowledged that red edge method has a potential to detect the existence of hazardous and toxic waste, in the case where the acid sludge waste detection is correlated with the land rehabilitation such as neutralization, bioremediation, solidification and non-activation of acid sludge in the contaminated area which can be observed from its spectral displacement. The detection is related to bioremediation implementation and the indication of acid sludge in contaminated area. Based on the executed review, the red edge method is potentially applicable for this activity. The red edge pattern has defined the contaminated area in Pertamina RU-V Balikpapan. Based on the obtained and reviewed data, this research concluded that the monitoring of condition of hazardous waste could be implemented to identify which hazardous waste has been treated.